217k views
5 votes
If f (x) = 2x + 1 and g(x) = x2 + 7. which of the following is equal to f(g(x)) ?

User Sansan
by
4.7k points

1 Answer

1 vote

You have the following functions:

f(x) = 2x + 1

g(x) = x² + 7

In order to find an expression for f(g(x)) you simply replace the function g(x) where x is in f(x), just as follow:

f(g(x)) = 2g(x) + 1 replace g(x) = x² + 7

f(g(x)) = 2(x² + 7) + 1 apply distribution property

f(g(x)) = 2(x²) + 2(7) + 1

f(g(x)) = 2x² + 14 + 1 simplify like terms

f(g(x)) = 2x² + 15

Hence, the expression for f(g(x)) is 2x² + 15

User Vida
by
5.2k points